Economic Analysis of HIV/AIDS Pandemic in Sub-Saharan Africa - Nýdrle, Tomáš; Ježek, Tomáš, 1940-2017; Běláčková, Vendula, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2009)
HIV/AIDS is a real threat for Sub-Saharan Countries. It increased adult mortality substantially. HIV/AIDS pandemic causes the death of the most productive part of affected population. Human capital passing on to future generations is limited. Low economic performance and income inequality induce higher HIV vulnerability. Contra wise HIV/AIDS has significant negative effect on the welfare of affected population. The sources of pandemic in Sub-Saharan Africa are not only social and cultural. Health and nutrition situation play considerable role. Holistic approach based on education, fidelity, abstinence and improvement of economic situation and moderate condom use (as the last way of prevention) seems to be an effective way of pandemic elimination.
Vedoucí práce: Tomáš Ježek
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2010
Rok obhajoby 2010
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses